Intravenous thrombolysis pretreatment and other predictors of infarct in a new previously unaffected territory (INT) in ELVO strokes treated with mechanical thrombectomy. (26th June 2019) - Goyal, Nitin; Tsivgoulis, Georgios; Chang, Jason J; Malhotra, Konark; Goyanes, Juan; Pandhi, Abhi; Krishnan, Rashi; Ishfaq, Muhammad F; Hoit, Daniel; Nickele, Christopher; Inoa-Acosta, Violiza; Katsanos, Aristeidis H; et al.
Abstract : Introduction: One uncommon complication of mechanical thrombectomy (MT) is an infarct in a new previously unaffected territory (infarct in new territory (INT)). Objective: To evaluate the predictors of INT with special focus on intravenous thrombolysis(IVT)pretreatmentbefore MT. Methods: Consecutive patients with emergent large vessel occlusion (ELVO) treated with MT during a 5-year period were evaluated. INT was defined using standardized methodology proposed by ESCAPE investigators. The predictors of INT and its impact on outcomes were investigated. Results: A total of 419 consecutive patients with ELVO received MT (mean age 64±15 years, 50% men, median baseline National Institutes of Health Stroke Scale score 16 points (IQR 11–20), 69% pretreated with IVT). The incidence of INT was lower in patients treated with combination therapy (IVTandMT) than in patients treated with MT alone, respectively (10% vs 20%; p=0.011). The INT group had more patients with posterior circulation occlusions than the group without INT (28% vs 10%, respectively; p<0.001). The rates of 3-month functional independence were lower in patients with INT (30% vs 50%; p=0.007). IVT pretreatment was not independently related to INT (OR=0.75; 95% CI 0.32 to 1.76), and INT did not emerge as an independent predictor of 3-month functional independence (OR=0.69; 95% CI 0.29 to 1.62) on multivariable logistic regression models. Location of posterior circulation occlusion was independently associated with a higher odds of INT (OR=3.33; 95% CI 1.43 to 7.69; p=0.005). Conclusions: IVT pretreatment is not independently associated with a lower likelihood of INT in patients with ELVO treated with MT. Patients with ELVO with posterior circulation occlusion are more likely to have INT after MT.